The Association Between Particulate Matter Air Pollution and Respiratory Health in Elderly With Type 2 Diabetes Mellitus. Issue 9 (September 2017) - Hao, Yanhui; Zhao, Jing; Wang, Kan; Feng, Nannan; Sun, Pin; Chen, Renjie; Han, Bin; Bai, Zhipeng; Zhu, Yiliang; Gao, Ying; Xia, Zhao-lin
Abstract : Objective: We investigated the association between respiratory health and particulate matter (PM) air pollution in elderly type 2 diabetes mellitus (T2DM) pre-, during, and post-the Chinese Lunar New Year (CLNY) holiday in Shanghai, China. Methods: We conducted repeated measurements of lung function and inflammation biomarker in a cohort consisted of 60 participants with T2DM. Results: Decreased PM2.5 exposure had an effect on respiratory health by increasing in forced expiratory flow in 1 second (FEV1 ) and forced vital capacity (FVC). Positive associations between PM exposure and exhaled nitric oxide (eNO) were observed. Conclusions: Our observations indicated that PM air pollution exposure would exert adverse effect on respiratory health in elderly T2DM population.